Immune Regulation, but Not Antibacterial Activity, Is a Crucial Function of Hepcidins in Resistance against Pathogenic Bacteria in Nile Tilapia (Oreochromis niloticus Linn.) - Pagaporn Phan-Aram; Gunanti Mahasri; Pattanapon Kayansamruaj; Piti Amparyup; Prapansak Srisapoome (Biomolecules, 2020)
In this study, the functions of a recombinant propeptide (rProOn-Hep1) and the synthetic FITC-labelled mature peptides sMatOn-Hep1 and sMatOn-Hep2 were analyzed. Moreover, sMatOn-Hep1 and sMatOn-Hep2 were mildly detected in the lymphocytes of peripheral blood mononuclear cells (PBMCs) and strongly detected in head kidney macrophages. The in vitro binding and antibacterial activities of these peptides were slightly effective against several pathogenic bacteria. Immune regulation by sMatOn-Hep1 was also analyzed, and only sMatOn-Hep1 significantly enhanced the phagocytic index in vitro (p < 0.05). Interestingly, intraperitoneal injection of sMatOn-Hep1 (10 or 100 µg) significantly elevated the phagocytic activity, phagocytic index, and lysozyme activity and clearly decreased the iron ion levels in the livers of the treated fish (p < 0.05). Additionally, sMatOn-Hep1 enhanced the expression levels of CC and CXC chemokines, transferrin and both On-Hep genes in the liver, spleen and head kidney, for 1–96 h after injection, but did not properly protect the experimental fish from S. agalactiae infection after 7 days of treatment. However, the injection of S. agalactiae and On-Heps indicated that 100 μg of sMatOn-Hep1 was very effective, while 100 μg of rProOn-Hep1 and sMatOn-Hep2 demonstrated moderate protection. Therefore, On-Hep is a crucial iron-regulating molecule and a key immune regulator of disease resistance in Nile tilapia.